Suzanne Césaire: la poétique de la responsabilité d’un sauvetage - Emina, Antonella (Ponti/Ponts, 2022)
This article analyses the work of Suzanne Césaire by bringing out the features of a literary sensibility and a critical thought that grasp the interdependence between mankind and the laws that regulate nature as well as all civilisation. This article is also a step in a long-standing path that originated in the analysis of the relationship between geography and francophone literature. It also benefits from the critical attention that moves from the evolution of landscape epistemology to ecopoetics. This article adds the contemporary concern for the connection of human, social and environmental well-being to the centrality given to natural spaces. All these suggestions are investigated through the essential principles of geopoetics and ecopoetics, because of their role in the debate about the presence of man on Earth, his responsibility as part of a vast network, and his fragility to be protected.